Utilizing Hybrid RO-OARO Systems as New Methods for Desalination Process - Hassan, Hassanain A.; Al-Alawy, Ahmed Faiq; Al-shaeli, Muayad (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The scarcity of fresh water and its essential role in sustaining life on Earth have motivated researchers to seek new, low-cost, scalable technologies for water desalination. Therefore, the osmotically assisted reverse osmosis (OARO) membrane process presents an innovative approach to achieve moderate water recoveries from high salinity water without undergoing a phase change. This work aims to investigate the performance of hybrid RO-OARO systems with various designs and operational parameters on recovery and R%. The hybrid systems were evaluated for 60 minutes at feed concentrations of 3.98-5.54 g/l, applied pressures ranging from 3 to 7 bars, and different membrane types. The results showed that the flux of the hybrid system increased by increasing the pressure and decreased by increasing the feed concentration. The highest recovery value was obtained for the RO-OARO system at an RO pressure of 7 bar and an OARO unit at 3 bar for a 3.98 g/l feed concentration. In contrast, when the reverse osmosis pressure was fixed at 5 bar, and the pressure of the OARO unit increased by 2 bar, the recovery value exceeded by about 6%. Furthermore, the FilmTech membrane showed the highest recovery at 31.7%, while the highest R% was 94.55% for the AquaTec membrane. The RO-OARO-OARO system contributed to increasing both the recovery and rejection values by 11.4 and 2.1%, respectively, compared with the RO-OARO system. The experiments in this study revealed a slight increase in the feed concentration of the reverse osmosis unit, indicating the efficiency of the hybrid systems compared to traditional RO systems.